Dispersal of Oxyops vitiosa: A Biological Control Agent of Melaleuca in Florida - William A. Overholt; Paul D. Pratt (EDIS)
In 1986, USDA/ARS scientists at the Invasive Plant Research Laboratory in Fort Lauderdale started a classical biological control program against melaleuca. The scientists recently released two insects as part of that program; the melaleuca weevil (Oxyops vitiosa (Coleoptera: Curculionidae)) and the melaleuca psyllid (Boreioglycapsis melaleucae (Hemiptera: Psyllidae)). This publication discusses the current distribution and dispersal rate of the weevil since in its introduction. This document is ENY-701, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2004.